Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.